2009
DOI: 10.1002/hep.23011
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite motif-containing 22 inhibits the activity of hepatitis B virus core promoter, which is dependent on nuclear-located RING domain

Abstract: Members of the tripartite motif (TRIM) family are a part of the innate immune system to counter intracellular pathogens. TRIM22 has been reported to possess antiretroviral activity. Here we report that TRIM22 is involved in antiviral immunity against hepatitis B virus (HBV). Our results showed that TRIM22, being a strongly induced gene by interferons in human hepatoma HepG2 cells, could inhibit HBV gene expression and replication in a cell culture system as well as in a mouse model system. Importantly, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(203 citation statements)
references
References 33 publications
11
180
2
5
Order By: Relevance
“…Because liver biopsy samples were not available, it is unclear whether TRIM22 was also induced in hepatocytes. Previous research 13 has demonstrated that TRIM22 is upregulated in liver cell lines, consistent with its up-regulation in PBMCs. In the present study, upregulation of TRIM22 was also observed in Huh-7 cells after IFNa treatment.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Because liver biopsy samples were not available, it is unclear whether TRIM22 was also induced in hepatocytes. Previous research 13 has demonstrated that TRIM22 is upregulated in liver cell lines, consistent with its up-regulation in PBMCs. In the present study, upregulation of TRIM22 was also observed in Huh-7 cells after IFNa treatment.…”
Section: Discussionsupporting
confidence: 73%
“…19,24,25 Gao and colleagues observed that TRIM22 was mainly localized in the nucleus of HepG2 cells when it suppresses HBV survival. 13 The discrepancy in localization compared to our present study may be due to the different cell lines we used (Huh-7 cell lines). The mechanism by which TRIM22 suppresses HCV replication is of substantial interest.…”
Section: Ifn-a-induced Trim22 Interrupts Hcv Replicationcontrasting
confidence: 81%
See 2 more Smart Citations
“…TRIM5, one of the host restriction factors blocking retroviral replication 44 , is located in a gene cluster in human with three other closely related TRIM genes, including TRIM6, TRIM34 and TRIM22. Genes in this cluster have also been suggested to inhibit the activity of HBV 45 . In the tree shrew, this gene cluster displays a dynamic evolutionary episode (Fig.…”
Section: Resultsmentioning
confidence: 99%